Increasing Adolescent Awareness About Mental Health Using Audiovisual Media - Romadhiyana Kisno Saputri; Ria Indah Kusuma Pitaloka; Kharisma Kusuma Wardani; Puji Aning Nur Nadhiffa (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Mental health in adolescents has recently become a serious concern because the prevalence of mental disorders in adolescents is increasing and today's youth are very vulnerable to mental disorders. Adolescent knowledge related to mental health can be increased by providing counseling using the right media. Audio-visual media, especially video, has proven to be more effective than other media in increasing adolescent knowledge. This community service activity aims to increase youth knowledge about mental health by using audiovisual media. Activities are carried out using counseling methods and audio-visual media, namely video. The result of the activity is an increase in target knowledge by 42%. Evaluation of the activities showed that 78% were very satisfied with the counseling activities and 86% were very satisfied with the material presented. Audio-visual media in the form of videos can increase adolescents' knowledge about mental health.